One Size does not fit all: The Learning Organisation comes to Singapore - Retna, Kala; Jones, Deborah (School of Management Working Papers, 2002)
In this paper, we question the cross-cultural validity of the key propositions of Learning Organization (LO) theory. Using two Singapore-based case studies, we argue that LO theory as promoted by Senge cannot be culturally neutral nor universally applicable. Rather, it includes a number of assumptions about both ’learning’ and ’organization’ that are specific to western cultural contexts. After describing the study and key findings, we present two differing commentaries: one from an ‘insider’, a Singaporean practitioner who is the fieldwork researcher, and one from an ‘outsider’ - a non-Singaporean (New Zealand) academic. Our research suggests that the key constructs of the LO are seen as attractive in same ways, but as going against the grain of what is seen as Singapore’s national culture, and that the tensions between ‘Learning Organization’ and ‘Singapore Culture’ make a thorough-going adoption of Senge’s LO principles in Singapore organizations to be impossible.